The Architecture of Endurance: A Systematic Review of SME Financial Sustainability in Emerging Markets - Amir Hamzah; Arief Rahman; Hadri Kusuma (Universitas Hayam Wuruk Perbanas, 2026)
The financial sustainability of small and medium-sized enterprises (SMEs) has become increasingly important in the context of economic volatility, technological disruption, and growing sustainability demands. However, existing studies remain fragmented and often examine financial, organizational, technological, and environmental factors in isolation. This study systematically reviews 49 articles indexed in the Scopus and Web of Science databases published between 2014 and 2026 to identify the dominant determinants, thematic patterns, and conceptual structure of financial sustainability in SMEs. Using the PRISMA protocol and NVivo-based bibliometric and thematic analyses, this study examines publication trends, geographic distribution, lexical structures, and thematic relationships across the literature. The results show that research is concentrated primarily in Asia and Europe, reflecting increasing scholarly attention to financial literacy, governance quality, resilience, digital transformation, FinTech adoption, ESG practices, and green finance. Thematic synthesis reveals three interconnected pillars—Internal Capability, Adaptive Resilience, and Digital–Green Transformation—which collectively form an architecture of endurance framework that explains how SMEs maintain financial viability under conditions of uncertainty and change. This framework advances prior reviews by integrating organizational capability, resilience-building mechanisms, and sustainability-oriented transformation into a unified model of financial sustainability for SMEs. Practically, the findings highlight the importance of strengthening financial literacy, governance quality, risk management capability, digital adoption, and sustainability-oriented financing, while emphasizing the role of policy support and financial inclusion in fostering SME resilience. Future research should further explore the implications of generative artificial intelligence, blockchain-based finance, and decentralized finance (DeFi) on SME financial sustainability.